Study the Dissociation Enthalpies for R134a Clathrate Hydrate in Binary and Ternary Systems - AL Mukhtar, Riyadh S.; AL Hemeri, Shurooq T.; Mahmood, Lina W. (Al-Khwarizmi Engineering Journal, 2018)
In the present work the clathrate hydrate dissociation enthalpies of refrigerant R134a+ water system, and R134a + water + salt system were determined. The heat of dissociation of three types of aqueous salts solutions of NaCl, KBr and NaF at three concentrations (0.09, 0.17and 0.26) mol·kg−1 for each salt type, were enthalpy measured. The Clapeyron equation was used tocalculate heat of dissociation of experimental data for binary and ternary system.In order to find the effect of compressibility factor on heat dissociation enthalpy, the study was conducted by using equation of state proposed by Peng and Robinson Stryjek-Vera (PRSV). The obtained results of dissociation enthalpy for binary system were (143.8) kJ.mol-1 without gas compressibility factor (z) and (136.08) kJ.mol-1 with z where the variation between two values was (5.3%). For ternary system (R134a+ water +NaCl) at three concentrations of this salt, the calculated values were in the range of (146.7 - 154.1) kJ.mol-1without z and (138.02-145.14) kJ.mol-1with z where the variation rang between two values was (5.8-5.7) %. The other two types of salts given similar results within (0.886 - 0.129) % deviation rang about NaCl results without z and (0.818-0.149) % deviation rang with z values.